Decolonizing Organizational Communication. (August 2022) - Pal, Mahuya; Kim, Heewon; Harris, Kate L.; Long, Ziyu; Linabary, Jasmine; Wilhoit Larson, Elizabeth; Jensen, Peter R.; Gist-Mackey, Angela N.; McDonald, Jamie; Nieto-Fernandez, Beatriz; Jiang, Jing; Misra, Smita; et al.
The ideas of this forum germinated at the Organizational Communication Division's pre-conference at the 106th annual convention of the National Communication Association (NCA) in 2020. A group of scholar-teachers, committed to addressing various critical social issues, came together to challenge dominant ideas, paradigms, and structures within and beyond organizational communication. We engaged with decolonization and social justice as an ongoing project that cultivates scholarship, pedagogy, and public engagement. Our discussions left us with a sense of urgency and inspiration to work substantively toward thinking differently about organizational communication. Our goal in this forum is to present the collective as a sharp provocation to decenter the spaces of theorizing and pedagogical practices in organizational communication and beyond.